Designing Persuasive Application to Promote Public Transportation Use - Thedy Yogasara; Vania Edra Christabel Naomi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2021)
The poor air quality of Jakarta, caused among others by fossil fuel combustion for transportation, harmfully affects the health of its people. Carbon emissions resulting from transportation activities can be reduced by getting people to use public transportation more frequently. This research aims at designing a persuasive application to encourage people to use public transportation more often. The steps of interaction design were employed. Firstly, user needs were identified using interviews, resulting in 48 interpreted needs which were then grouped into nine primary needs. Secondly, a design workshop involving users and designers was conducted to produce three concept alternatives. In the next stage, the best concept was selected using the concept scoring method and was subsequently refined through the SCAMPER method. A high-fidelity prototype was developed based on the final concept. Lastly, the evaluation process of the application prototype named ecoGlide consisted of two major parts, i.e. the evaluation of performance and persuasive qualities. The performance evaluation was conducted through Usability Testing using five criteria. The effectiveness and efficiency criteria consecutively score 91% and 71.43%, exceeding the minimum acceptable value of 70%. Furthermore, the satisfaction, usefulness, and learnability criteria respectively score 3.83, 3.88, and 3.88, which surpass the threshold value of 3.4. The persuasive quality was evaluated using the qualitative method through a coding scheme. The result shows that the Emotion and Persuasion categories were most closely related to the application use. The most influential sub-category of the persuasion aspect is Reward Driven, which ranks 4th out of 14 sub-categories. Overall, the ecoGlide application was considered to have good usability and persuasive ability.